On sequencing two types of tasks on a single processor under incomplete information - Burnetas, AN; Katehakis, M.N. (Probability in the Engineering and Informational Sciences, 1993)
Two types of tasks are to be scheduled on a single processor under incomplete information about the task lengths. We derive the structure of optimal scheduling rules w.r.t. flowtime, as well as asymptotic approximations for a large number of tasks, when the length distributions belong to a one-parameter exponential family. © 1993, Cambridge University Press. All rights reserved.